Ethanol and Caffeine Effects on Social Interaction and Recognition in Mice: Involvement of Adenosine A2A and A1 Receptors - López-Cruz, Laura; San-Miguel, Noemí; Bayarri, Pilar; Baqi, Younis; Müller, Christa E.; Salamone, John D.; Correa, Mercé (Frontiers in Behavioral Neuroscience, 2016)
Ethanol and caffeine are frequently consumed in combination and have opposite effects on the adenosine system: ethanol metabolism leads to an increase in adenosine levels, while caffeine is a non-selective adenosine A1/A2A receptor antagonist. These receptors are highly expressed in striatum and olfactory tubercle, brain areas involved in exploration and social interaction in rodents. Ethanol modulates social interaction processes, but the role of adenosine in social behavior is still poorly understood. The present work was undertaken to study the impact of ethanol, caffeine and their combination on social behavior, and to explore the involvement of A1 and A2A receptors on those actions. Male CD1 mice were evaluated in a social interaction three-chamber paradigm, for preference of conspecific vs. object, and also for long-term recognition memory of familiar vs. novel conspecific. Ethanol showed a biphasic effect, with low doses (0.25 g/kg) increasing social contact and higher doses (1.0-1.5 g/kg) reducing social interaction. However, no dose changed social preference; mice always spent more time sniffing the conspecific than the object, independently of the ethanol dose. Ethanol, even at doses that did not change social exploration, produced amnestic effects on social recognition the following day. Caffeine reduced social contact (15.0-60.0 mg/kg), and even blocked social preference at higher doses (30.0-60.0 mg/kg). The A1 antagonist CPT (3-9 mg/kg) did not modify social contact or preference on its own, and the A2A antagonist MSX-3 (1.5-6 mg/kg) increased social interaction at all doses. Ethanol at intermediate doses (0.5-1.0 g/kg) was able to reverse the reduction in social exploration induced by caffeine (15.0-30.0 mg/kg). Although there was no interaction between ethanol and CPT or MSX-3 on social exploration in the first day, MSX-3 blocked the amnestic effects of ethanol observed on the following day. Thus, ethanol impairs the formation of social memories, and A2A adenosine antagonists can prevent the amnestic effects of ethanol, so that animals can recognice familiar conspecifics. On the other hand, ethanol can counteract the social withdrawal induced by caffeine, a non-selective adenosine A1/A2A receptor antagonist. These results show the complex set of interactions between ethanol and caffeine, some of which could be the